2021
DOI: 10.1038/s41565-021-00886-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastics are neither microplastics nor engineered nanoparticles

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
301
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(336 citation statements)
references
References 60 publications
(73 reference statements)
2
301
0
Order By: Relevance
“…On the basis of this review work, it is considered more appropriate for the analysis of nanoplastics to follow the approach used for engineered nanomaterials rather than that for microplastics [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of this review work, it is considered more appropriate for the analysis of nanoplastics to follow the approach used for engineered nanomaterials rather than that for microplastics [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in real samples a mix of polymers can be found and the composition, additives, and characteristic products of each polymer are difficult to distinguish from each other [46]. As the plastic size decreases, the contribution of organic matter/microbial increases influencing the transport, uptake, and accumulation pathways of NPs [34]. Furthermore, the nanoscale size limits chemical analysis techniques; all the techniques that are popular in MPs analysis have a limited application for NPs.…”
Section: Simulated Samples-laboratory Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most in vitro toxicological studies use polystyrene (PS) NPs as model particles and, for the most part, toxicity is only observed at high concentrations or following longterm exposure, unless the NPs are endowed with a positive surface charge, as is the case for amino-functionalized PS NPs which were shown to be toxic towards a range of cell types (Anguissola et al, 2014;Mrakovcic et al, 2014;Ruenraroengsak and Tetley, 2015;Hesler et al, 2019;He et al, 2020). Notwithstanding the fact that spherical NPs may not be representative of the heterogenous features of plastic debris (Gigault et al, 2021), the question remains whether traditional cell culture models are suitable for the evaluation of nanoplastics. Cho et al (2011) investigated cellular uptake of gold NPs using upright and inverted cell culture configurations and found that uptake depends on the sedimentation and diffusion velocities and is independent of size, shape, density, and surface coating of the NPs.…”
Section: Introductionmentioning
confidence: 99%